Peran Kompetensi Kepribadian Guru Terhadap Pembentukan Pendidikan Karakter Peserta Didik - Eneng Sumarni; Kun Nurachadijat (Politeknik Kampar, 2023)
This study aims to describe the role of teacher personality competence on the character of students at SDIT Adzkia 1 Sukabumi, Research methods using qualitative methods of data collection techniques are carried out with interview, observation and documentation techniques. Based on the data obtained, teacher personality competence greatly influences the attitude of students both in behavior and speech both in the school environment and outside the school. A good personality carried out by a teacher will provide a good example to students, the teacher will be a figure who obeys all his wisdom, advice, speech and commands. The personality competency of the teacher is expected to shape the character of students, so that the implementation of learning can run well and teachers can transfer their knowledge and can be accepted by students.